Implikasi keberadaan agens hayati Neochetina eichhorniae (Coleoptera: Curculionidae) terhadap eceng gondok - Sapdi Sapdi; Damayanti Buchori; Utomo Kartosuwondo; S. Tjitrosemito; Bandung Sahari (Jurnal Entomologi Indonesia, 2007)
The effectiveness of Neochetina eichhorniae as a biocontrol agent of waterhyacinth was evaluated in West Java and DKI Jakarta. The objective of this research was to study the implication of the existence of N. eichhorniae on waterhyacinth. Research was conducted in several freshwater ecosystem infested by waterhyacinth and N. eichhorniae, including Cibinong and Lido lakes (Bogor District), Muara Angke Sanctuary (North Jakarta), and Citarum Hulu river (Purwakarta District), conducted during April to August 2004. The impact of N. eichhorniae on waterhyacinth was evaluated by leaf damage intensity and growth parameter of the plant. Results showed that there was no correlation between waterhyacinth and the occurrence of the N. eichhorniae. The population of N. eichhorniae adults was significantly low in any locations studied. Thus, the existence of the biocontrol agent can not result in decreasing of waterhyacinth population.